Peningkatan Pelayanan Publik Pemerintah Desa Melalui Sistem Running Text - Fadhli, Khotim; Deva, Rendy Nur; Putra, Saiful Aminudin Alkusuma; Munawaroh, Siti; Setiawan, Deny; Firmansya, Aditiya Bayu; Saputra, Dimas Arif; Khumaini, A. Syauqi; Prayoga, Wilda (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The application of running text technology at the Ketapangkuning Village Hall aims to increase the efficiency of disseminating public information which so far still relies on conventional methods. This program is implemented using a community service method which includes several stages, namely planning through a needs survey, installing running text technology in strategic locations, training village officials in operating the system, and evaluating the effectiveness of implementing this technology. With running text, important information such as meeting schedules, announcements and public services can be displayed in real-time and repeatedly, making it easier for the public to access. This program also equips village officials with technological skills to manage the system independently. The results of the implementation show an increase in the transparency of public services, the effectiveness of meetings, and community participation in village activities. Overall, this system has succeeded in supporting better, open and accountable village governance, and has the potential to become a model for other villages with similar challenges in disseminating public information.